Age Differences in Preferences for Fear-Enhancing Vs. Fear-Reducing News in a Disease Outbreak - Villalba, Anthony A.; Stanley, Jennifer Tehan; Turner, Jennifer R.; Vale, Michael T.; Houston, Michelle L. (Frontiers in Psychology, 2020)
Older adults prefer positive over negative information in a lab setting, compared to young adults (i.e., positivity effects). The extent to which older adults avoid negative events or information relevant for their health and safety is not clear. We first investigated age differences in preferences for fear-enhancing versus fear-reducing news articles during the Ebola Outbreak of 2014. We were able to collect data from 15 young adults (YA) and 13 older adults (OA) during this acute health event. Compared to YA, OA were more likely to read the fear-enhancing article, select hand-sanitizer over lip balm, and reported greater fear of Ebola. We further investigated our research question during the COVID-19 pandemic with 164 YA (18-30 years) and 171 OA (60-80 years). Participants responded to an online survey about the COVID-19 pandemic across 13 days during the initial peak of the pandemic in the United States. Both YA and OA preferred to read positive over negative news about the coronavirus, but OA were even more likely than YA to prefer the positive news article. No age differences in the fear of contraction were found, but OA engaged in more health-protective behaviors compared to YA. Although OA may not always report greater fear than YA or seek out negative information related to a health concern, they still engage in protective health behaviors. Thus, although positivity effects were observed in attention and emotional reports (in the COVID-19 study), OA still modified their behaviors more than YA (give-away in both studies, and health-protective behavior change in the COVID-19 study), suggesting that positivity effects did not hamper OA ability to respond to a health crisis.